Development of the multidimensional health perceptions questionnaire in English and Spanish - Shannon B. Juengst; Marlene Vega; Alexandra B. Holland; Susan Herrera; Robin T. Higashi; Maria Boix Braga; Alka Khera; Chung Lin Kew; Valeria Silva (SpringerOpen, 2022)
Abstract Purpose To develop the novel multidimensional health perceptions questionnaire (MHPQ), a self-reported assessment of health perceptions inclusive of (1) individuals beliefs about the causes and consequences of health conditions, benefits and barriers to maintaining and improving health, ability to accomplish health-related goals and control health circumstances, and the role of God and/or spirituality in health and healthcare, (2) anticipated discrimination in the healthcare systems, and (3) trust in healthcare providers and medicine, illustrated in our newly proposed Multidimensional Health Perceptions Conceptual Model. Methods We developed an initial MHPQβ item set, corresponding to domains of our conceptual model, using a patient-centered outcomes development approach. This include literature review, expert and end-user feedback, translation and language validation (specifically to Latin American Spanish), and cognitive interviewing. Results The initial 104 items of MHPQβ had excellent content validity, with a Content Validity Index of 98.1%. After expert (n = 13) feedback, translation and language validation, and cognitive interviewing among community-dwelling English-speakers (n = 5) and Spanish-speakers (n = 4), the final MHPQβ comprised 93 items rated on a five-point agreement scale (1 = Strongly disagree to 5 = Strongly agree), with a reading grade level of 6th grade in English and 8th grade in Spanish. Conclusion The MHPQβ is a promising tool to assess individuals' health perceptions. It has excellent content validity and good reading accessibility. Future work will establish the factor structure and final item set of the MHPQ.